War of words Britain, France and discourses of empire during the Second World War - Chin, Rachel 1987- (Cambridge University Press, 2022)
War of Words argues that the conflicts that erupted over French colonial territory between 1940 and 1945 are central to understanding British, Vichy and Free French policy-making throughout the war. By analysing the rhetoric that surrounded these clashes, Rachel Chin demonstrates that imperial holdings were valued as more than material and strategic resources. They were formidable symbols of power, prestige and national legitimacy. She shows that having and holding imperial territory was at the core of competing Vichy and Free French claims to represent the true French nation and that opposing images of Franco-British cooperation and rivalry were at the heart of these arguments. The selected case studies show how British-Vichy-Free French relations evolved throughout the war and demonstrate that the French colonial empire played a decisive role in these shifts
Title from publisher's bibliographic system (viewed on 11 Jul 2022)
From the Dunkirk evacuations to the Franco-German armistice: renegotiating the Franco-British alliance -- "The real question at issue": British policy and the French fleet -- A necessary tragedy? the British bombardments of the French fleet at Mers el-Kébir -- Vichy, the free French and the battle for imperial influence at Dakar in September 1940 -- Promises of independence: Operation Exporter and the struggle for the Levant -- Operation Torch: American influence and the battle for French North Africa -- Independence on French terms: the 1943 Lebanese Parliamentary Crisis -- Holding on to empire: the French bombardment Of Damascus, May 1945
Keywords: World War, 1939-1945 / Great Britain / Diplomatic history; World War, 1939-1945 / France / Diplomatic history; Great Britain / Foreign relations / France; France / Foreign relations / Great Britain; Great Britain / Foreign relations / 1936-1945; France / Foreign relations / 1914-1940; France / History / German occupation, 1940-1945